1972
DOI: 10.1017/s0021859600026241
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the quality of forage from its cell-wall content and amount of cell wall digested

Abstract: Grasses and legumes comprising poor to good quality temperate and tropical species were fed to either cattle or sheep in 36 digestibility experiments. Cell wall in these forages was the ash-free and protein-free residue after sequential extraction with acidpepsin, organic solvents and either water for grasses or ammonium oxalate for legumes. The average amount of cell wall digested per 100 g forage OM was 40-0 + 0-59 g in grasses and 19-8 ± 1-85 g in legumes. It was considered that within grasses and within le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 11 publications
4
13
0
Order By: Relevance
“…Digestible cell-wall values of 41 and 37 % for the two grasses were close to 40 % of forage OM, as has been found in other grasses (Moir, 19726). At 14% of forage OM, apparently undigested total cellular contents were only a little higher than values found by Moir, Laws & Blight (1975).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Digestible cell-wall values of 41 and 37 % for the two grasses were close to 40 % of forage OM, as has been found in other grasses (Moir, 19726). At 14% of forage OM, apparently undigested total cellular contents were only a little higher than values found by Moir, Laws & Blight (1975).…”
Section: Discussionsupporting
confidence: 78%
“…With suitable equipment the sequential procedure is adaptable to large-scale work and it has been used in a number of studies of forage digestibility. Moir (19726) found by this procedure that digestible cell wall (% cell wallx% digestibility/100) was relatively constant at about 40% of forage organic matter (OM) over a wide range of both temperate and tropical grass species. The apparently undigested cellular contents varied only between 9 and 13% of forage OM (Moir, 1974;Moir, Laws & Blight, 1975).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that the proportion of should be made up as far as feasible with cell content cell content is lower and the digestibility of cell wall (which is quickly available and has a positive effect on higher in perennial than in Italian ryegrass (Wilman intake) rather than with cell wall (which is digested & Wright 1978 a, b). more slowly and can restrict intake) (Moir 1972; Italian ryegrass may be higher than perennial Osbourn et al 1974) and there should be an ryegrass in water-soluble carbohydrate (WSC) appropriate balance of soluble carbohydrate and (Spedding & Diekmahns 1972) and perennial ryegrass protein, probably with a higher proportion of soluble may be higher than meadow fescue (Dent & Aldrich carbohydrate than is commonly found (Beever 1993(Beever ). 1963Moller et al 1973).…”
mentioning
confidence: 99%
“…Animal physiology also plays an important role (Moir 1972). It has been shown that Camelidae use fibre more efficiently than sheep (Kayouli et a1 1991).…”
Section: Animal Physiologymentioning
confidence: 99%